Pengembangan Aplikasi Kamus Bahasa Melayu Dialek Ketapang dengan Implementasi Algoritma Binary Search - Atimi, Rizqia Lestika; Orama, Rizky; Ruhibnur, Refid (Indonesian Society of Applied Science, 2023)
As a country that is rich in ethnic, cultural and linguistic diversity, Indonesia has 668 vernacular languages, one of them is Malay. West Kalimantan is one of the regions in Indonesia where majority of the population is Malay. The population used Malay language with a variety of dialects distinctive regional. The Ketapang Malay dialect is used in Ketapang Regency. Vernacular languages which are inherited from the ancestors should be preserved as an effort to maintain their function and position as ethnic identity, personality, as well as a means to show the variety of regional culture. Unfortunately, along with the times and influx of foreign cultural influences to Indonesia as an impact of globalization, many words of Malay Ketapang dialect underwent changes, developments and displacements, moreover leading to extinction. This research developed an Android-based application of Ketapang Malay Dictionary (KBMK) with the implementation of the binary search algorithm. Application was developed using following method, data collecting, application development, application testing, and system evaluation. Blackbox testing shows that the binary search algorithm is able to search the keyword correctly. Furthermore, the KBMK application was tested using a usability evaluation, evaluation obtained an average score of 4.48 indicating that the application is useful and effective in conducting searches, and providing user satisfaction.